Antimicrobial Effect of Cannabidiol on Intracellular Mycobacterium tuberculosis - Maffia, Paulo César (Mary Ann Liebert, 2024)
Mycobacterium tuberculosis, the etiologic agent of tuberculosis (TB), has killed nearly one billion people during the last two centuries. Nowadays, TB remains a major global health problem ranked among the top 10 causes of death worldwide. One of the main challenges in developing new strategies to fight TB is focused on reducing the duration and complexity of drug regimens. Cannabidiol (CBD) is the main nonpsychoactive ingredient extracted from the Cannabis sativa L. plant, which has been shown to be biologically active against bacteria. The purpose of this work was to investigate the antimicrobial effect of CBD on M. tuberculosis intracellular infection.
Keywords: Ciencias naturales::Ciencias biológicas::Biología celular, Microbiología